Monitoring of atmospheric parameters in Ukraine and at the Antarctic station Akademik Vernadskiy: the urgency of research, equipment, and development concept - E. I. Terez; V. M. Vaschenko; S. O. Dolgiy; A. V. Kozak; S. V. Kuzmin; G. A. Terez; E. I. Loza; Zh. I. Patlashenko (Ukrainian Antarctic Journal, 2008)
The Ukrainian Antarctic station Akademik Vernadskiy is proposed to be used as background station with minimal aerosol quantity. It is shown that in conditions of high latitude stations the determination of atmosphere optical density by Bouguer-Langley method may lead to high error. Hence it is expediently to use photometric apparatus with absolute calibration. Such calibration should be held regularly before and after antarctic observations at atmospheric station with good astroclimate conditions (in Crimea).